Туркман ва қорақалпоқ адабиётида Навоий анъаналари - Қурамбоев, К (FAN va JAMIYAT, 2021)
The artiete deals with the impact of the work by Alisher Navoiy in Turkmen and Karakalpak classic as well as modern literature, cre-